The Sensory Threshold: ‘Femmage’ as Politics of the Surface - Tartaglia, Raffaella (SigMa - Rivista di Letterature comparate, Teatro e Arti dello spettacolo, 2025)
This article investigates the sensory and material role of the surface, approaching it through the conceptual and formal lens of Melissa Meyer and Miriam Schapiro’s concept of femmage (1977-78). Drawing on concepts of indexicality, haptic visuality, and feminist visual theory, the study explores how the surface operates not only as a boundary between image and viewer but as an agentive site of meaning. Tracing femmage from 1970s feminist collage practices to contemporary post-digital assemblages, the study offers close readings of works by Su Friedrich, Susan Stein, Anne Bean, and Sara Cwynar. It argues that strategies of fragmentation, layering, and close-up construct surfaces that do not merely show, but perform.